Changes in Saliva Analytes in Pigs in Different Clinical Situations from Farms Positive to Porcine Reproductive and Respiratory Syndrome (PRRS): A Pilot Study - Eva Llamas-Amor; Silvia Martínez-Subiela; Fernando Tecles; Aida Miralles; Elena Goyena; Andrea Martínez-Martínez; José Joaquín Cerón; Alberto Muñoz-Prieto (Viruses)
Porcine reproductive and respiratory syndrome (PRRS) is aworldwide spread disease. This study analyzed the changes in saliva analytes of pigs infected with PRRS virus (PRRSV) in different clinical conditions that can appear in PRRSV-positive farms. Biomarkers for inflammation (haptoglobin, total proteins), immune response (adenosine deaminase), tissue damage (lactate dehydrogenase), stress (alpha-amylase), and sepsis (calprotectin, aldolase, Serpin B12) were measured in pigs under three clinical scenarios: (1) no evident clinical signs, (2) clinical signs indicating PRRSV activation, and (3) secondary bacterial infection by Streptococcus suis. Haptoglobin and lactate dehydrogenase showed significant increases in pigs with PRRSV activation compared to pigs without clinical signs. Additionally, the levels of Serpin B12, aldolase, calprotectin, total proteins, and the activity of adenosine deaminase significantly increased in pigs with meningitis compared to pigs without clinical signs, but did not show significant differences between healthy pigs and those with PRRSV clinical signs without bacterial infection. In summary, PRRSV-infected pigs can show differences in selected saliva analytes depending on their clinical condition. These findings may have practical applications for detecting PRRSV infections and differentiating cases with associated meningitis.